The Influence of Automated Harvest Robots in Japan on the Interest of TRPL IPB Students in Improving the Welfare of Agriculture - Manurung, Maryetha Yovanka Leony; Kirana Sya'bani, Salsi; Septia Anggraeni , Ika; Ummah, Khaera; Sacio Ramadhani , Amelia; Fathul Mubin , Ardi; Fuad Rahmatid Dhuha, Muhammad; Rubina Lestari, Humannisa (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2024)
This study aims to examine the impact of Automated Harvesting Robots on agriculture in Japan and to investigate how the interest of TRPL IPB students in these technologies might influence agricultural innovation in Indonesia. The research evaluates how these robots have transformed agricultural practices in Japan by enhancing efficiency, reducing labour costs, and alleviating labour shortages. It also explores the potential for these advancements to stimulate agricultural innovation in Indonesia, facilitated by the engagement of TRPL IPB students. A mixed-methods approach was employed, combining an analysis of agricultural productivity and labour data from Japan with surveys and focus groups involving TRPL IPB students. This methodology comprehensively assesses the technological advancements and their implications for both Japanese and Indonesian agricultural sectors. Findings indicate that Automated Harvesting Robots have substantially improved efficiency and lowered labour costs in Japan while addressing labour shortages. These outcomes suggest that similar technologies could be beneficial if adopted in other regions. The high level of interest among TRPL IPB students reflects a readiness to integrate such innovations into Indonesian agriculture. Their feedback on the functionality of these robots offers valuable insights into their perceptions and potential barriers to technology adoption. The study highlights the critical role of technological exchange and student involvement in fostering agricultural innovation. However, limitations include potential cultural and infrastructural differences between Japan and Indonesia that may affect the direct applicability of these technologies. Future research should address these challenges and explore strategies to adapt and implement these innovations across diverse agricultural contexts effectively.